Middle Wisconsinan Mammals, Stratigraphy, and Sedimentology at the Ketza River Site, Yukon Territory - Jackson, Lionel; Harington, C. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTRemains of Middle Wisconsinan mammoth, bison, horse, moose, hare, ground squirrel and lemming were recovered from sediments that stratigraphically underlie till of the Late Wisconsinan McConnell Glaciation along the Ketza River valley. The bone-bearing sediments are a complex of colluvium, fan, and outwash sediments. Similar fossil sites are likely to occur where glaciofluvial watercourses abut hillside deposits laid down prior to the onset of McConnell Glaciation.